The impact of crisis management in achieving banking liquidity: applied research in a sample of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Crises affect the economic growth of the country in general and the banking sector in particular. Given the importance of this sector, it is necessary to evaluate the performance of banks from time to time and monitor the liquidity of each bank and how to organize its management to overcome any crisis or emergency situation that may befall it. The research seeks to diagnose the level of impact of crisis management. In the liquidity of Iraqi private banks, using liquidity indicators, as the research community represents the banks listed in the Iraq Stock Exchange As for the research sample, it is represented by (10) private banks that were chosen from among (21) banks listed in the Iraq Stock Exchange that comply with the research requirements and for the period (2012-2020) using the annual data. A set of variables and financial ratios were used to measure the liquidity of the banks, the research sample during the crisis period, to analyze the relationship between the research variables and test the research hypotheses. And its continuous development to keep pace with changes in the economic environment to face risks and crises, which has a positive impact on the safety and security of the banking sector.